PERAN BRIEF KONTEN DALAM MENYELARASKAN PENYAMPAIAN PESAN DAN VISUALISASI KONTEN DIGITAL DI TRANS MEDIA SOSIAL - Nafra Alyssa Syahbaniah; Aceng Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Internal communication management in the digital creative industry often faces message distortion between the ideation team and the visual execution team. This study aims to analyze the role of written content briefs in aligning message delivery and digital content visualization at Trans Media Sosial (TMS). The methodology employed is descriptive qualitative, with data collected through in-depth interviews with mentors, graphic designers, and video editors, alongside participatory observation and document study. The results indicate that digital platform-based written briefs act as an effective dual quality control instrument. In the messaging aspect, this document successfully locks in information accuracy and content pillars derived from collective team brainstorming. In the visual aspect, the use of concrete descriptive sentences effectively guides the designers' layouts and aligns video scene sequences transparently. The existence of the brief is proven to significantly reduce repetitive revisions and accelerate daily production turnaround. In conclusion, this study underscores the importance of standardized written blueprints as an alignment tool for both conceptual and practical aspects to maintain message integrity.